Enhancing Assessment Practices and Teaching Delivery in Honors Research Projects - Lloyd, Natalie; Bland, K. (2015)
A teaching excellence project initiated by the authors aims to enhance student engagement and outcomes in the Bachelor of Civil and Construction Engineering cap-stone research units; Civil Engineering Research Project 1 and 2, is reported here. The aim will be achieved through the enhancement of teaching, assessment and scholarship of teaching and learning. The aim will assist with the continued improvement of the Units as articulated in the School Plan (for unit satisfaction rates to exceed 80%). The project is currently underway with implementation of significant changes in Project 1 and Project 2 units in semester 1, 2015 (February – July) with faculty and student preliminary feedback indicating enhancement of teaching and learning, and collegial relationships.